2021
DOI: 10.1111/jpc.15531
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, aetiology and outcome of paediatric ocular trauma in Sydney

Abstract: Aim: Report epidemiology, aetiology and outcomes of eye injuries in children 0-16 years treated at quaternary referral and paediatric hospitals in Sydney, Australia. Methods: A retrospective review of cases January 2009 to December 2015 using hospital diagnostic and International Classification of Diseases, 10th Revision codes. Medical records confirmed open globe injury (OGI) or closed globe injury (CGI) diagnosis and demographic, injury mechanism, ocular and best-corrected visual acuities (BCVA) before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…Although the visual outcome demonstrated a statistically signi cant improvement after the treatment in our study, the mean VA of 0.83 ± 1.13 logMAR at the last visit displays a considerable loss compared to normal vision in terms of visual ability of the children. This nding is supported also by many other studies in the literature focusing on pediatric ocular trauma 5,11,23 . The undesirable visual outcome after pediatric ocular traumas despite of the advancements in microsurgery points out to the signi cance of further preventive measures reducing the probability and severity of ocular injuries in order to avoid substantial visual morbidity in children.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Although the visual outcome demonstrated a statistically signi cant improvement after the treatment in our study, the mean VA of 0.83 ± 1.13 logMAR at the last visit displays a considerable loss compared to normal vision in terms of visual ability of the children. This nding is supported also by many other studies in the literature focusing on pediatric ocular trauma 5,11,23 . The undesirable visual outcome after pediatric ocular traumas despite of the advancements in microsurgery points out to the signi cance of further preventive measures reducing the probability and severity of ocular injuries in order to avoid substantial visual morbidity in children.…”
Section: Discussionsupporting
confidence: 81%
“…presented a similar relationship in their studies, as well 5,6 . According to the ndings of Liu et al, however, the presence of a vitreous hemorrhage was also found to be a poor prognostic factor; about which we did not record any signi cant relationship in the present study 5 .…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations